(untitled) (GEOMATE Journal, 2017)
In light of the significance of the three spot gourami (Trichogaster trichopterus Pallas, 1770) as a widely consumed main protein source, this research identifies and characterizes the parasites, especially those with the harmful health effects, residing in this fish species of the Thung Lam reservoir in Thailand’s northeastern province of Buriram. In the study, a total of 120 three spot gourami fish samples were examined and the findings revealed the presence of three parasitic species. Two external parasitic species were found in the gill filaments: Trianchoratus aecleithrium and Gyrodactylus sp., and another one in the intestines: Pallisentis nagpurensis. The discovery of the three host-specific parasitic species shows no clinical signs of disease in the fish, despite the presence of parasites on their fish hosts. It is also the case that fish-borne helminthic infections are commonplace in Thailand. Furthermore, these parasites could conveniently be eliminated by adequate cooking. Thus, to minimize the parasites-induced health risks, it is recommended that the fish must be thoroughly cooked prior to consumption.